Cutting EDGE: pre-intermediate students'BOOK with DVD-ROM - Cunningham, S. Sarah (Pearson Education Limited, 2013)
Cutting Edge Third Edition builds on the distinctive task-based approach that has made this course so popular. Engaging texts, new video content and a comprehensive digital package are just some of the features that make this fully revised edition even more effective.